Analisis Kesulitan Belajar dalam Memahami Materi Barisan Ditinjau dari Kemampuan Pemecahan Masalah Matematis - Abel Purnama; Ilham Falani; Nurul Hidayah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Low mathematical problem-solving ability causes students to experience various difficulties in understanding arithmetic sequences and series. This study aimed to analyze students’ learning difficulties and the factors influencing them in terms of mathematical problem-solving ability. A descriptive qualitative approach was employed involving Grade X E3 students of SMA Negeri 17 Merangin. Data were collected through mathematical problem-solving tests, interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings revealed that students experienced conceptual, representational, procedural, and strategic difficulties, with varying levels across problem-solving ability categories. Students with low problem-solving ability demonstrated the most dominant difficulties in all aspects. The factors contributing to learning difficulties consisted of internal and external factors. These findings indicate that enhancing mathematical problem-solving ability should become a primary focus of mathematics instruction to reduce students’ learning difficulties.